Ukraine 22 : Ukrainian writers respond to war - Andryczyk, Mark (2023)
On 24 February 2022, the lives of Ukrainians were devastatingly altered. Since that day, many of Ukraine's writers have attempted to fathom what is happening to them and to their country. This anthology brings together writing from inside Ukraine, by Ukrainians, available in English for the first time. Here they document everyday life, ponder the role of culture amid conflict, denounce Russian imperialism and revisit their relations with the world, especially Europe and its ideals, as they try to comprehend the horrors of war